The Effect Of Internal Audit Implementation And Risk Management On Lending Policies People's Business In The Covid-19 Period At PT. Bank Sumut Centre Medan - Duma Megaria Elisabeh; Farida Sagala; Ivo Maelina Silitonga; Rintan Br Saragih; Anggiat Manurung (Jurnal Ilmiah Accusi, 2024)
This study aims to examine the effect of the implemention of internal audit and risk management on the policy of granting people’s business loans in the covid-19 period. In this study using primary data in the form of distributing questionnaires conducted at PT Bank Sumut Pusat Medan, the sampling technique used was purposive sampling with data collection techniques using a questionnaire method. The analysis used in this study uses the methods of validity, reability, data normality, classical assumptions, coefficient of determination t test and f test. The results of this study indicate that internal audit has a partial effect on the policy of granting people’s business loans at covid-19 with a tcount value of 7.472 at a significant level 0f 0.003. Risk management partially affects the policy of granting people’s business credit during covid- 19 with a tcount value of 7.432 with a significant level of 0.000. Internal audit and risk management simultaneously affect the policy of granting people’s business loans during covid-19 with a fcount value of 92.717 with a significant value of In addition, the adjusted R square value of 0.859 means that internal audit (X1) and risk management (X2) together affect the policy of granting people’s business loan during covid-19 by 85.9% while the remaining 14.1% is influenced by other variables outside of this study